Vigilância genômica do SARS-CoV-2 em Betim, Minas Gerais - Diego Menezes Bonfim (2021)
Coronaviruses (CoVs) are positive strand RNA viruses that constitute the subfamily Orthocoronavirinae. Seven different types of CoV are capable of infecting humans, including the Betacoronavirus SARS-CoV-2, closely related to strains that infect bats, its probable zoonotic origin. The new coronavirus has polymorphisms in its genome, specially in its gene encoding the spike surface protein, used to infect human cells through the ACE-2 receptor, and is associated with the development of the new pandemic disease named COVID-19. Originating in China at the end of December 2019, SARS-CoV-2 had its first confirmed case of infection in Brazil on February 26, 2020 and in the state of Minas Gerais on March 4, 2020. Constant genomic surveillance strategies are important to control the transmission and spread of the virus in the human population. With the emergence of SARS-CoV-2 variants of interest (VOI) and concern (VOC), the local and global scenario of the pandemic has become more complex, which reinforces the need for this type of study. The goal of this dissertation was to carry out the genomic surveillance of SARS-CoV-2 in the city of Betim-MG, the fifth most populous city in the state, with industrial importance and crossed by state and federal roads receiving a considerable human migratory flow. For this, a total of 3239 nasopharyngeal swab samples collected from June to July 2020 were tested by RT-qPCR for SARS-CoV-2, sorted for sequencing on the MiSeq platform (Illumina) using an amplification-based methodology with primers covering the whole SARS-CoV-2 genome. In the end, 35 new SARS-CoV-2 genomes were obtained (coverage > 79%; depth > 200x). These genomes were included in phylogenetic reconstructions to identify circulating viral lineages, dated phylogeographic models, interpolation to analyze dispersion patterns and genetic maps to visualize polymorphisms. Of the 35 genomes obtained, 18 (51.4%) were classified as lineage B.1.1.28 and 17 (48.6%) as lineage B.1.1.33, circulating in the first phase of the pandemic in the state of MG. The unrooted phylogenetic model confirmed the lineages and suggested multiple introductions for both clades. The phylogeographic models suggested at least 7 and 12 distinct introductions for the B.1.1.28 and B.1.1.33 lineages, respectively. Geographic dispersion models show the spread of the pandemic over time, but do not suggest geographic patterns for each lineage. We highlight a B.1.1.33 genome that presents 12 specific mutations and that is positioned at a considerable distance compared to the others in the phylogeographic model of this strain. The results suggest an interstate migration flow of the human population in the dispersion of SARS-CoV-2, fact that must be taken into account when adopting measures to control the pandemic in the city of Betim-MG.